11q24.2q24.3 microdeletion in two families presenting features of Jacobsen syndrome, without intellectual disability: Role of FLI1, ETS1, and SENCR long noncoding RNA. Issue 6 (19th March 2019) - Conrad, Solène; Demurger, Florence; Moradkhani, Kamran; Pichon, Olivier; Le Caignec, Cédric; Pascal, Cécile; Thomas, Caroline; Bayart, Sophie; Perlat, Antoinette; Dubourg, Christèle; Jaillard, Sylvie; Nizon, Mathilde
Abstract : This report presents two families with interstitial 11q24.2q24.3 deletion, associated with malformations, hematologic features, and typical facial dysmorphism, observed in Jacobsen syndrome (JS), except for intellectual disability (ID). The smallest 700 Kb deletion contains only two genes: FLI1 and ETS1, and a long noncoding RNA, SENCR, narrowing the minimal critical region for some features of JS. Consistent with recent literature, it adds supplemental data to confirm the crucial role of FLI1 and ETS1 in JS, namely FLI1 in thrombocytopenia and ETS1 in cardiopathy and immune deficiency. It also supports that combined ETS1 and FLI1 haploinsufficiency explains dysmorphic features, notably ears, and nose anomalies. Moreover, it raises the possibility that SENCR, a long noncoding RNA, could be responsible for limb defects, because of its early role in endothelial cell commitment and function. Considering ID and autism spectrum disorder, which are some of the main features of JS, a participation of ETS1, FLI1, or SENCR cannot be excluded. But, considering the normal neurodevelopment of our patients, their role would be either minor or with an important variability in penetrance. Furthermore, according to literature, ARHGAP32 and KIRREL3 seem to be the strongest candidate genes in the 11q24 region for other Jacobsen patients.